CONDITIONING RELIGIOUS CULTURE TO IMPROVE RELIGIOUS CHARACTER AND DISCIPLINE AT MI NURUL MUN'IM PAITON PROBOLINGGO - Azizah, Ella Shofiatun (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Character development is very important to form a good person. The character development process can be carried out through certain programs. This research aims to understand and improve the effectiveness of religious character and discipline education in the younger generation, as well as exploring methods that can be used to achieve the desired goals. Classified as a type of field research ( Field Research ) with qualitative research methods. In this research, data was obtained using interview, observation and documentation techniques. The informants in this research were the principal, teachers and students at MI Nurul Mun'im. The data collection technique uses a data reduction process, data presentation and verification. With this refraction, the research shows the importance of religious activities in forming religious character and discipline in students. Apart from that, this research also highlights the challenges in implementing character education in schools and concrete efforts that can be made to increase its effectiveness.